Quorum sensing and virulence of Pseudomonas aeruginosa during urinary tract infections - (:unkn) unknown (My University, 2012)
Introduction: In the opportunistic pathogen Pseudomonas aeruginosa, the production of several virulence factors depends on quorum sensing (QS) involving N-acylhomoserine lactone signal molecules. In vitro studies have suggested that the QS system is crucial in the pathogenesis of P. aeruginosa. However, it is unclear whether QS systems of P. aeruginosa play the same role during infections. Methodology:  In this study, to explore the contribution of QS systems to the pathogenesis of P. aeruginosa during urinary tract infections, we collected 82 clinical isolates. Detection of N-acyl-homoserine lactones (C12-HSL and C4-HSL) was performed on agar plates employing biosensor strains C. violaceum. Elastase and biofilm production were determined spectrophotometrically. QS genes were detected by PCR and subsequently underwent sequencing. Results and conclusion:  Six isolates were found to be negative in the production of both C12-HSL and C4-HSL and all virulence factors tested.  PCR analysis of these isolates revealed that four isolates contained all four QS genes while one isolate was negative for lasR gene, and one isolate negative for lasI, lasR and rhlR genes. Sequence analyses of these isolates showed that the lasR, lasI, rhlR and rhlI genes had point mutations. The combination of these mutations probably explains their C12-HSL, C4-HSL and virulence factor deficiencies. Results of this study suggest that QS deficient clinical isolates occur and are still capable of causing clinical infections in humans.